Imagining Australia : (Distributed by Harvard university committee on Autralian studies, 2004)
Beginning in the last third of the twentieth century, Australian literary and cultural studies underwent a profound transformation to become an important testing ground of new ideas and theories. How do Australian cultural products project a sense of the nation today? How do Australian writers, artists, and film directors imagine the Australian heritage and configure its place in a larger world that extends beyond Australia's shores